BACTERIOLOGICAL PROFILE OF SURGICAL SITE INFECTIONS AND THEIR ANTIBIOGRAM: A STUDY IN A TERTIARY CARE HOSPITAL - NIHARIKA; SAPNA BATRA; LOVEENA OBEROI (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: To ascertain the frequency of surgical site infection (SSI) occurrences and the prevalence of aerobic bacterial infections associated with their antibiogram. Methods: For 1 year, a tertiary care hospital affiliated with Government Medical College, Amritsar, served as the site of this cross-sectional study. Pus aspirates were aseptically taken from 86 consecutive individuals suspected of having SSI using a sterile surgical syringe with a needle and sterile cotton surgical swabs. The specimens were cultivated and placed in an incubator at 37°C for 24 h. The individual strains were then identified using traditional techniques. The Kirby–Bauer’s Disc Diffusion Method was employed to conduct antimicrobial susceptibility testing. Results: Among 1021 patients, 86 were clinically suspected of SSI, and 64 were culture-positive. The incidence of SSI was 8.42%. The most common organisms were Klebsiella pneumoniae 34% (17/50) and Escherichia coli 32% (16/50), whereas Staphylococcus aureus 100% (14/14) was the only organism found among Gram-positive cocci. The antimicrobial Profile of Gram-positive isolates showed maximum sensitivity to linezolid (100%), followed by erythromycin (85.7%). The antimicrobial profile of lactose fermenters revealed maximum sensitivity to polymyxin (100%). Antibiogram of Proteus species showed maximum sensitivity to meropenem (100%) and ceftazidime tazobactam (100%). Non-fermenters showed 100% polymyxin and 80% sensitivity to aztreonam. Conclusion: Our study has revealed significant findings. The incidence of SSI was found to vary between 8% and 12% in our tertiary care center. K. pneumoniae 26.5% (17/64) and E. coli 25% (16/64) were the most common organisms isolated. S. aureus 21.2% (14/64) was the only organism found among Gram-positive cocci. SSI below waist surgery was far more 75% (48/64) than above waist surgery of 25% (16/64).